Thailand as a Tourism Destination: Factors Influencing Wellness Tourism Intentions of Chinese Older Adults - Cheng, Jiebei; Jiang, Songyu; Phakdeephirot, Nutteera (Ann Publisher, 2025)
Background. Thailand, with its rich natural resources, traditional healing therapies, and high-quality healthcare services, has become an attractive destination for Chinese senior tourists. Aim. This study integrates the Health Belief Model (HBM) and Push-Pull Theory to examine the key determinants influencing older Chinese adults' intention to engage in wellness tourism in Thailand. Methods. A quantitative approach was adopted, utilizing a structured questionnaire covering perceived susceptibility, perceived severity, perceived benefits, perceived barriers, push factors, pull factors, and wellness tourism intention. Data were collected through stratified random sampling across eastern, central, and western regions of China, using both online (WeChat, Wenjuanxing) and offline (senior activity centers, community health centers) methods. 462 valid responses were analyzed using structural equation modeling (SEM).Result. The results indicate that perceived benefits positively influence wellness tourism intention, while perceived barriers significantly reduce it. Both push and pull factors enhance wellness tourism intention, with their interaction exerting an even more substantial effect. However, contrary to HBM’s conventional assumptions, perceived susceptibility and perceived severity negatively impact wellness tourism intention, suggesting that heightened health concerns may deter older adults from traveling. Conclusion. This study extends the application of HBM and refines the Push-Pull Theory in the wellness tourism context. Practically, it offers insights for policymakers and industry stakeholders to develop targeted wellness tourism services. Furthermore, this study lays a theoretical foundation for future research by offering an integrative model that captures both health-related perceptions and tourism motivations.Implementation. The findings deepen the understanding of how health perceptions and travel motivations interact to influence senior tourists’ wellness tourism decisions.